Managing the Pandemic in the South Asian (SAARC) Countries - Venkat Rao Pulla; Aisha Shoukat; Muhammad Jafar; Md. Fakhrul Alam; M.T.R. Shamini Attanayak; Jabeen Mussarat; Gyanendra Gautam; Rachel Lafain; Sanjay Prasad (Space and Culture, India, 2022)
This paper explores the coronavirus pandemic response from a South Asian perspective. When their case numbers were still relatively low, the South Asian Association for Regional Cooperation (SAARC) countries adopted lockdowns at the same time or before India did. On 24 March 2020, when there were just two confirmed cases, Nepal went into lockdown, and Sri Lanka locked down on 22 March, when there were 78 cases. India locked down the day after Nepal, with all countries imposing some form of restrictions on people’s movement. This paper draws its data from the first year of the pandemic that loomed in the SAARC nations. The regional cooperation provided by SAARC has allowed the sharing of resources and a strengthening of the region’s self-reliance. Notably, the commitment made by India to ensure its neighbours are supplied with vaccines, many of these donated. The eight-member SAARC states are Afghanistan, Bangladesh, Bhutan, India, Maldives, Nepal, Pakistan, and Sri Lanka.